Recurrent Fusions Between YAP1 and KMT2A in Morphologically Distinct Neoplasms Within the Spectrum of Low-grade Fibromyxoid Sarcoma and Sclerosing Epithelioid Fibrosarcoma - Puls, Florian; Agaimy, Abbas; Flucke, Uta; Mentzel, Thomas; Sumathi, Vaiyapuri P.; Ploegmakers, Marieke; Stoehr, Robert; Kindblom, Lars Gunnar; Hansson, Magnus; Sydow, Saskia; Arbajian, Elsa; Mertens, Fredrik (American Journal of Surgical Pathology, 2020)
Sclerosing epithelioid fibrosarcoma (SEF) is an aggressive soft tissue sarcoma. In the majority of cases, there is overexpression of MUC4, and most cases show EWSR1-CREB3L1 gene fusions. A subset of SEF displays composite histologic features of SEF and low-grade fibromyxoid sarcoma (LGFMS). These "hybrid" tumors are more likely to harbor the FUS-CREB3L2 fusion, which is also seen in most LGFMS. We, here, characterize a series of 8 soft tissue neoplasms with morphologic features highly overlapping with LGFMS and SEF but lacking MUC4 expression and EWSR1/FUS-CREB3L gene fusions. Seven tumors showed fusions of the YAP1 and KMT2A genes, and 1 had a fusion of PRRX1 and KMT2D; all but 1 case displayed reciprocal gene fusions. At gene expression profiling, YAP1 and KMT2A/PRRX1 and KMT2D tumors were distinct from LGFMS/SEF. The patients were 4 female individuals and 4 male individuals aged 11 to 91 years. Tumors with known locations were in the lower extremity (5), trunk (2), and upper extremity (1); 3 originated in acral locations. Tumor size ranged from 2.5 to 13 cm. Proportions of SEF-like and LGFMS-like areas varied considerably among tumors. All tumors that showed infiltrative growth and mitotic figures per 10 HPFs ranged from 0 to 18. Tumor necrosis was present in 1 case. Follow-up was available for 5 patients (11 to 321 mo), 2 of whom developed local recurrences, and 1 died of metastatic disease. The clinical behavior of these soft tissue sarcomas remains to be further delineated in larger series with extended follow-up; however, our limited clinical data indicate that they are potentially aggressive.
CRIS-Team Scopus Importer:2020-04-28